The Pre-Informing Approach and a Synthesis of Existing Prompting Techniques for Improving Output Quality in Black-Box Large Language Models (Third Sector Social Economic Review, 2026)
This study proceeds from the premise that the effectiveness of Large Language Models (LLMs) in synthetic data generation depends not only on model capacity but also on the quality of human-guided prompting strategies. Within this framework, it reviews twenty-three prompt-writing techniques reported in the literature and proposes a hybrid approach, pre-informing, which aims to improve output quality through structured contextual preparation before the main instruction. The study comparatively evaluates zero-shot and pre-informing prompting across 20 education-domain text-generation tasks, using 3 black-box LLMs: ChatGPT 5.2 Standard, Gemini 3 Fast, and Claude Sonnet 2.6. This design yields a total of 120 generated outputs.The outputs are evaluated through a common quantitative framework consisting of Word Count, Unique Word Count, Average Sentence Length, and Technical Terms Count. The internal coherence of this indicator set is supported by a standardized Cronbach’s alpha of .887. Descriptive comparisons show that the pre-informed condition yields higher values across all four indicators. These differences are further confirmed by Wilcoxon signed-rank tests, which show statistically significant improvements across all four measures. In addition, Friedman test results indicate that the magnitude of improvement differs significantly across models, with Claude showing the largest overall gains, Gemini the most limited gains, and ChatGPT generally occupying an intermediate position.The findings indicate that pre-informing is associated with stronger output quality as reflected in measurable indicators, and that its effects are observable across multiple task types rather than being limited to isolated examples. At the same time, the results show that the effectiveness of pre-informing is not uniform across black-box LLMs and remains partly model-sensitive. The study positions pre-informing as a structured and reproducible prompt-based framework for improving quality-related output characteristics and underscores the continuing importance of human guidance in shaping LLM outputs.
Keywords: Large Language Models; Prompt Design; Prompt Engineering; Synthetic Data Generation; Black-box LLMs